Influence of posttreatment irrigation timings and herbicide placement on bermudagrass and goosegrass (Eleusine indica) response to low-dose topramezone and metribuzin programs. Issue 2 (27th March 2022) - Brewer, John R.; Craft, Jordan C.; Askew, Shawn D.
Abstract: Immediate posttreatment irrigation has been proposed as a method to reduce hybrid bermudagrass [ Cynodon dactylon (L.) Pers. × Cynodon transvaalensis Burtt Davy] phytotoxicity from topramezone. Immediate irrigation is impractical, because it would take a turfgrass sprayer 10 to 15 min to cover an average golf course fairway or athletic field. There is also insufficient evidence regarding how posttreatment irrigation, immediate or otherwise, influences mature goosegrass [ Eleusine indica (L.) Gaertn.] control from topramezone or low-dose topramezone plus metribuzin programs. We sought to investigate bermudagrass and E. indica response to immediate, 15-min, and 30-min posttreatment irrigation compared with no irrigation following topramezone at 12.3 g ae ha −1, the lowest labeled rate, or topramezone at 6.1 g ha −1 plus metribuzin at 210 g ai ha −1 . We also evaluated placement of each herbicide and their combination on soil, foliage, and soil plus foliage to help elucidate the mechanisms involved in differential responses between species and herbicide mixtures. Responses were largely dependent on trial due to bermudagrass injury from high-dose topramezone being nearly eliminated by immediate irrigation in one trial and only slightly affected in another. When posttreatment irrigation was postponed for 15 or 30 min, topramezone alone injured bermudagrass unacceptably in both trials. Bermudagrass was injured less by low-dose topramezone plus metribuzin than by high-dose topramezone. All posttreatment irrigation timings reduced E. indica control compared with no posttreatment irrigation. The herbicide placement study suggested that topramezone control of E. indica is highly dependent on foliar uptake and that phytotoxicity of both bermudagrass and E. indica is greater from topramezone than metribuzin. Thus, posttreatment irrigation likely reduces topramezone rate load with a concomitant effect on plant phytotoxicity of both species. Metribuzin reduced 21-d cumulative clipping weight and tiller production of plants, and this may be a mechanism by which it reduces foliar white discoloration from topramezone.